Professional Liability of Land Deed Officials and the Evidentiary Degradation of Materially Defective Grant Deeds: An Examination of Religious Court Decisions - Aini, Sella Nur; Abdullah, Zaitun; Riyanto, Astim (SIGn Jurnal Hukum, 2026)
The transfer of land rights through a grant instrument is absolutely limited to a maximum of one-third of the estate to protect the heirs’ legitime (legitieme portie). The violation of this material limitation strongly correlates with the negligence of Land Deed Officials and culminates in judicial disputes, as reflected in the jurisdictional anomaly between the Lumajang Religious Court Decision and the Surabaya High Religious Court Decision. This research aims to analyze the construction of the public official’s juridical liability and examine the degradation of the deed’s evidentiary value due to material defects. Through normative legal research employing case, statute, conceptual, and philosophical approaches, this study finds that the Land Deed Official’s failure to apply the prudential principle is qualified as negligence, implicating the emergence of administrative, civil, and ethical liability. Furthermore, exceeding the grant limit renders the legal act null and void, thereby degrading the deed’s evidentiary value to a private deed and nullifying its validity in state administrative affairs. However, the appellate court decision was rigidly bound by procedural formalism, refusing to adjudicate the case (déni de justice) on grounds of administrative jurisdiction. As a legal prescription, the religious court should annul the material act of the grant to revert the object into the undivided whole estate (boedel waris). This object’s status serves as a basis for requesting restoration to the original state (restitutio in integrum) at the Land Office. Supreme Court intervention through jurisprudence is required to align administrative certainty with the value of justice in wealth preservation (hifz al-mal).